PENDIDIKAN ISLAM DI INDONESIA: RESTROPEKSI DAN PROYEKSI MODERNISASI PENDIDIKAN ISLAM DI INDONESIA - Sutarman Sutarman (Al-Misbah (Jurnal Islamic Studies), 2013)
Modern Islam Education in Indonesia are generally are influenced by Muhammadiyah organization. As we know that organization of Muhammadiyah has many schools from the Playgroup until the University. Not only Muhammadiyah, NU organization also gives some contribution of education in Indonesia, especially a boarding school. Not only both of the private organization which give some contributions in education, there are also manyÂ  pionirs of Islamic education in Indonesia that have given the contributions, as like Ki Hajar Dewantara, Harun Nasution, Mukti Ali,Â  Malik Fajar, etc. They dreamed to the generation that would combine intellectualâ€ enlightenmentâ€ with pure spirituality, wisdom, and continuous activism. Being extraordinarily knowledgeable in religious and social sciences and familier with principle of material sciences. So, the equilibrium for society are able to be gotten.